1996
DOI: 10.1111/j.1440-1673.1996.tb00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary small‐cell carcinoma of the oesophagus with spontaneous oesophageal perforation following chemotherapy

Abstract: The authors describe a 66 year old woman with small-cell carcinoma of the oesophagus who developed a perforation following chemotherapy. Small-cell carcinoma of the oesophagus is a rare neoplasm, varying in appearance from a small mucosal lesion to a larger fungating mass, which in our patient presented as a bulky soft-tissue mass causing stricture. Pleural fluid collections which developed via a spontaneous oesophageal-pleural fistula were subsequently drained using percutaneously placed catheters. Radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…The esophageal perforation resulted in esophagopleural fistula. However, their patient was discharged after esophageal stenting [14]. Ohtsu et al reported a patient having SCCE with an esophagomediastinal fistula.…”
Section: Discussionmentioning
confidence: 97%
“…The esophageal perforation resulted in esophagopleural fistula. However, their patient was discharged after esophageal stenting [14]. Ohtsu et al reported a patient having SCCE with an esophagomediastinal fistula.…”
Section: Discussionmentioning
confidence: 97%
“…The prognosis is excellent with conservative treatment [6]. Intramural hematoma of the esophagus can also be misdiagnosed as other digestive pathologies such as perforated peptic ulcer and pancreatitis [6], cardiac or vascular diseases such as ischemic heart disease, dissection or aneurysm rupture of the thoracic aorta [3] or pulmonary embolism [9], or pulmonary lesions such as pneumothorax [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Esta alternativa de tratamento proposta por Casas e colegas, permitiu uma sobrevida de 6 anos em um paciente (24). Ainda tomando como base o uso de quimioterapia de forma semanal, por um período não inferior a 16 semanas, seguido de fungóide (17). optando por uma conduta radical mesmo nos casos de doença metastática.…”
Section: -Introduçãounclassified